Social norms vs socioeconomic vulnerability: Gender identity and female labor force participation in Ecuador - Jorge Yepez; Sara Caria (PLoS ONE, 2026)
Despite recent advances in reducing the gender gap globally, female labor force participation is still lower compared to men’s. Discriminatory social norms, such as the one that assigns to men the role of breadwinners, are important drivers of this difference. Building on the social prescription that “a man should earn more than his wife”, we explore the effect that relative income potential has on female engagement in the labor market in Ecuador. Results show that women with potentially higher relative income tend to increase their labor force participation (LFP), which is counter-intuitive with respect to the male breadwinner hypothesis. However, we find a differentiated effect according to women’s education and income level. More educated women do not increase their LFP, but tend to shift towards more precarious positions (informal or part-time); women with secondary education increase both their LFP and precariousness; women with only primary education, associated to lower income, increase LFP but do not increase precariousness, which is already quite high. These findings suggest that socio-economic characteristics of households condition the adherence to social norms.